Mechanism of defect formation during friction spot joining of 3D-printed TC4 alloy and ultra-high molecular weight polyethylene. (October 2020) - Zou, X.; Jiang, M.Y.; Chen, K.; Chen, B.X.; Reddy, K.M.; Zhang, S.Y.; Kondoh, K.; Wang, M.; Hua, X.M.; Zhang, L.T.; Shan, A.D.
Abstract: For the purpose of developing high-quality metal/polymer joints without defects to satisfy the strict requirement of biomedical application, 3D printed TC4 alloy was joined with non-polar ultra-high molecular weight polyethylene (UHMWPE) via friction spot joining (FSpJ). In this study, five sets of experiments with different joining temperatures were designed to figure out the formation mechanisms of defects. The joining temperature (TJ ) histories were measured with K-type thermocouple inserted in the lap interface. Macro−/micro-scale defects in TC4/UHMWPE joints were analyzed. Numerical simulation was carried out to study the temperature distribution during joining and gap formation during cooling. Micro−/nano-scale interfacial bonding was characterized using scanning electron microscope and transmission electron microscope. Then, the formation mechanisms of defects were better understood. Macro-scale defects were shown as insufficient filling and bubbles. Insufficient filling is linearly related to the TJ which can be alleviated by applying higher TJ . However, when the TJ is >385 °C, large bubbles appear due to excessive and fast thermal degradation of UHMWPE. Meanwhile, micro-scale defect, appearing as continuous gaps caused by the shrinkage of polymer can be avoided by enhancing the micro-scale interfacial bonding. Graphical abstract: Unlabelled Image Highlights: The formation mechanisms of defects in the TC4/UHMWPE joints which were categorized into macro- and micro-scale were better understood. Intimate atomic contact between TC4 and UHMWPE via an interfacial loose oxide layer was achieved. Generation of -C=O bonds in UHMWPE was found during joining through oxidative degradation, which can potentially facilitate TC4/UHMWPE bonding.